Pengaruh Corporate Governance Perception Index dan Ukuran Perusahaan Terhadap Harga Saham Perusahaan-Perusahaan yang Terdaftar di The Indonesian Institute of Corporate Governance dan Bursa Efek Indonesia - Suhartono Suhartono; Edy Suryadi; Dedi Hariyanto (Universitas Muhammadiyah Pontianak, 2018)
The background in this study aims to determine whether there is a partial and simultaneous influence between the Corporate Governance Perception Index (CGPI) and company size on the company's stock price listed in the Indonesian Institute for Corporate Governance (IICG) and the Indonesia Stock Exchange (IDX) period 2014-2016. The sampling technique uses purposive sampling method with a sample of 12 companies that are routinely registered during the 2014-2016 period at IICG and BEI. The method of data collection used is through descriptive research with a quantitative approach. The results of the study show multiple regression equations where Y = -4,266 + 0,30X1 + 0,511X2. Correlation coefficient value (R) is 0.773, so it can be concluded that the relationship between CGPI and company size on stock prices is strong. The results of the R square determination coefficient are 0.597. The partial test results of the influence of firm size can be concluded that the firm size variable does not have a significant effect on stock prices. The partial test results of the influence of CGPI can be concluded that the CGPI variable has a significant effect on stock prices. The results of the f test in testing this hypothesis are shown that together the independent variables have a significant influence on the dependent variable. This can be proven from the Fcount value of 24.447 greater than Ftable of 3.280. So it can be concluded that the CGPI variable and company size have a significant influence on stock prices